2016
DOI: 10.1080/09638288.2016.1211758
|View full text |Cite
|
Sign up to set email alerts
|

The role of empowerment and quality of life in depression severity among unemployed people with affective disorders receiving mental healthcare

Abstract: An empowerment approach and strategies, which support the quality of life, are needed in development of vocational rehabilitation interventions, and bridging of mental healthcare and vocational services. Implications for Rehabilitation Enhancing empowerment and quality life in the return to work process can decrease depression severity in unemployed people with affective disorder. There is a need to address work issues in addition to symptom reduction in primary and mental healthcare. Bridging the service and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
0
21
1
1
Order By: Relevance
“…It has also been argued by McAllistar and colleagues [35] that empowerment serves as an essential outcome measure for patients with long-term health conditions. Because empowerment is associated with both well-being and rehabilitation among persons with mental health problems [36,37] efforts to enhance empowerment is suggested as one crucial part of mental health treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been argued by McAllistar and colleagues [35] that empowerment serves as an essential outcome measure for patients with long-term health conditions. Because empowerment is associated with both well-being and rehabilitation among persons with mental health problems [36,37] efforts to enhance empowerment is suggested as one crucial part of mental health treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason closer to the circumstances of the individual could be the time and service gap between the mental health care and the vocational rehabilitation as seen in the TVR approach. This could impact on the depression in a negative way and prolong or delay a positive outcome [ 7 ] when in contemporary society work is a measure of value and success. Lower occupational function can lead to social exclusion [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have reported that cognitive dysfunction, age, psychosis, unemployment, suicide ideation are associated with depression severity ( 11 13 ). However, to our knowledge, there is a lack of a systematic study on the relationship between DMS-5 symptoms and depression severity.…”
Section: Introductionmentioning
confidence: 99%